Fibroline: a mobile app for improving the quality of life of young people with fibromyalgia - De la Vega, Rocío; Roset, Román; Galán, Santiago; Miró, Jordi (Journal of health Psychology, 2018)
Fibroline is a mobile application with a self-administered cognitive behavioral treatment for young people with fibromyalgia or chronic widespread pain, designed to reduce pain and other common negative symptoms and improve quality of life. Our aims are to report on the usability and feasibility protocols used to assess the app. Two usability cycles were implemented. A group of patients followed the cognitive behavioral treatment intervention to test its feasibility. Qualitative data were collected and content analyses were conducted. The results demonstrated that the app is error-free, easy to use, liked by the users, and acceptable.
Keywords: Fibromialgia; Chronic widespread pain; Cognitive behavioral treatment; Fibromyalgia; mHealth; Young people